Personal, social and professional support for newly qualified teachers: Teacher induction in Austria. (January 2023) - Symeonidis, Vasileios; Haas, Elisabeth; Schneider, Klaus
Abstract: This article analyses the perceptions of newly qualified teachers (NQTs) in Tyrol, Austria of the support received and challenges faced during the induction phase. A mixed-methods approach was used to collect data via a survey (N = 101) and interviews with NQTs (N = 13). Our findings show that NQTs found the personal and social support they received more helpful than the professional support, and regression analysis reveals that the perceived quality of the professional support was related to NQTs' overall judgement of the induction phase. The main challenges facing NQTs included high workload, combining studies with work, and irregular meetings with mentors. Highlights: We examine the kind of support that NQTs received during the teacher induction phase. NQTs perceive the personal and social support received more positively than the professional support provided. NQTs' perceptions of the professional support received is significant for the success of induction programmes. NQTs' main challenges include high workload, studying in parallel to working and irregular meetings with mentors.